Study on compressive strength of lightweight concrete filled with cement-reinforced epoxy Macrospheres and basalt fibers. (October 2022) - Jiang, Tao; Wang, Ying; Shi, Shanshan; Yuan, Nan; Wu, Xinfeng; Shi, Danda; Sun, Kai; Zhao, Yuantao; Li, Wenge; Yu, Jinhong
Abstract: In this work, cement-reinforced epoxy macrosphere (CR-EMS), hollow glass microspheres (HGMS) and basalt fibers (BF) were filled into the cement matrix and lightweight concrete was prepared by a combination of the ball rolling method and the molding method. The variation in the properties of lightweight concrete by influencing factors such as stacking volume fraction, number of layers and diameter of CR-EMS and HGMS's types, content and length of BF in the matrix were studied. The experimental results indicate that when the matrix is filled with 2 wt% of 15 mm BF and CR-EMS-9–10 mm-2layers-90 %, the density and maximum compressive strength of the composite are 1.143 g/cm 3 and 14.63 MPa, respectively. Compared to concrete with no BF added and with 0.5 % BF (9 mm) added, the compressive strength increased by 96 % and 61 %, respectively. The addition of BF tends to form a network connection effect, reduces the probability of brittle fracture of concrete, and helps to inhibit the generation of abrupt cracks.